Learning to construct authorial voice through citations: A longitudinal case study of L2 postgraduate novice writers. (June 2022) - Sun, Qingyang; Kuzborska, Irena; Soden, Bill
Abstract: The construction of authorial voice through citations is an important criterion for judging the success of students' academic writing. Students are required to distinguish a diversity of other views or voices advanced in texts, including their own, and to adopt an identity as an author that maintains the control of other voices. Thus, while a complex undertaking, the construction of voice also requires the reflection and reshaping of self as learners. Learners need to compare their existing knowledge of writing with the writing demands of their new disciplinary communities and revise it to meet those demands. Relatively little is known, however, about the process of such construction. To fill this gap, this study focused on ten Chinese students enrolled in a one-year master's programme in a UK university and examined their rhetorical purposes for source use over time, while also comparing source use by academic score. Students' course assignments and their dissertation literature review chapters were collected and analysed using an adapted framework following Petrić (2007) and Swales (1990). To understand students' citation practices, discourse-based interviews with students were also employed. The results from the text analysis showed that students tended to use citations primarily for knowledge display but less for comparing and contrasting sources and evaluating them, although more of the latter were made in their literature review chapters. The thematic analysis of the discourse-based interviews further revealed the influence of complex factors of citation use. These were students' language proficiency, reading skills, subject knowledge, their commitment to and time limit on coursework writing, and their beliefs about themselves as learners and knowledge construction.